On Automorphism Groups of Some Particular Groups - Hossain, Mohd Altab; Majumdar, Subrata (Journal of Bangladesh Academy of Sciences, 2016)
The cyclic groups, the additive group Q of rational numbers and the additive group R of real numbers are sometimes very useful elements in many studies. In this paper, the authors concentrated their intuition in determining the structures of the automorphism groups of these useful groups in the light of previous works. Journal of Bangladesh Academy of Sciences, Vol. 40, No. 2, 109-115, 2016